Exploring Students’ Higher Order Thinking Skills (HOTS): Best Practice in 13 Curriculum at Islamic High School in Bengkulu - Riswanto, Riswanto (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
In order to apply what has been learnt in a contemporary situation, Higher Order Thinking Skills (HOTS) serve as a metaphor for transferring knowledge and skills. Curriculum 2013 places emphasis on these diverse higher order thinking processes. This study intended to examine what challenges students at Islamic High School in Bengkulu had while using HOTS to answer questions about reading and what caused them to still make mistakes in this situation. The research was descriptive in nature. Techniques of data collection subsumed observation, interviews, and documentation. The results demonstrated that the students still struggled with word misinterpretation at the analysis stage. They had a hard time understanding the information in the provided text during the evaluating stage, and they also struggled to analyze the questions’ intentions. The students had a hard time coming up with concepts for new items during the creation stage. The second discovery demonstrated that the elements such as time, students’ mastery, students’ learning abilities, and the learning environment should all be taken into account. This study concluded that some of these issues, including obstacles, may be to blame for students' poor aptitude for solving HOTS-based problems. This study contributes to providing English academicians with the demographic picture of students’ challenges and factors related to HOTS. Untuk menerapkan apa yang telah dipelajari dalam situasi kontemporer, keterampilan berpikir tingkat tinggi berfungsi sebagai metafora untuk mentransfer pengetahuan dan keterampilan. Kurikulum 2013 menekankan pada beragam proses berpikir tingkat tinggi ini. Penelitian ini bermaksud untuk mengkaji tantangan apa yang dimiliki siswa Madrasah Aliyah Bengkulu saat menggunakan HOTS untuk menjawab pertanyaan tentang membaca dan apa yang menyebabkan mereka masih melakukan kesalahan dalam situasi tersebut. Penelitian ini bersifat deskriptif. Metode pengumpulan data kualitatif meliputi observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa subjek masih berkutat dengan kesalahan interpretasi kata pada tahap analisis. Individu kesulitan memahami informasi dalam teks yang disediakan selama tahap evaluasi, dan mereka juga berjuang untuk menganalisis maksud pertanyaan. Ketiga subjek mengalami kesulitan untuk menghasilkan konsep item baru selama tahap pembuatan. Penemuan kedua adalah bahwa unsur-unsur seperti waktu, penguasaan siswa, kemampuan belajar siswa, dan lingkungan belajar semuanya harus diperhitungkan. Peneliti dapat menarik kesimpulan bahwa beberapa masalah ini, termasuk hambatan, mungkin menjadi penyebab rendahnya kemampuan siswa dalam memecahkan masalah berbasis HOTS. Penelitian ini memeberikan akademisi Bahasa Inggris tentang gambaran demografi terkait tantangan dan faktor HOTS siswa.